Transparency in Educational Institutions as the Key to Successfully Addressing Sexual Violence Crimes in Higher Education - Aprilia Hana Pratiwi; Hwian Christianto; Tiara Prameswari (Dinasti Research, 2026)
Sexual Violence is considered a disgrace for Education Units. Protective steps to protect the good name of educational units are also carried out in various ways so that they make cases of sexual violence unresolved and tend to experience repeated. Normative juridical research methods review the regulation of legal provisions in Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence and Permendikbud 30/2021 on the one hand is associated with Higher Education policies on the other hand showing the inconsistency of Universities when handling cases of sexual violence. Research shows that universities that cover up sexual violence actually show inconsistencies in handling sexual violence. Ironically, efforts to cover up disgrace actually make the trust of the academic community and the community disappear to universities. Acts of sexual violence raise important legal issues, the importance of learning human dignity and dignity is not an object of sexual satisfaction.